The social construction of the "enemy" in a post 911 era - Janzen, Christina (University of Ottawa (Canada), 2008)
Who is the enemy in the post-9/11 period? Do we as a society build the enemy's identity, and if so how? This thesis explores the types of discourse, including binary opposition, and practices, including labelling and profiling, used by the media in the building of enemy identities. Using a qualitative research approach, I analyze over ninety articles from The Province, a Canadian newspaper, to investigate how one print media presented enemies in the thirty days following the World Trade Centre bombing on September 11, 2001. After situating my analysis within two overlapping theoretical perspectives, the critical discourse and the social constructionist perspectives, I demonstrate that the label of "enemy" is applied by society and the state to an entity that appears to pose a threat---I underline that appearing "different" can qualify a person or group for arbitrary surveillance among other human rights violations. My research will show that the issue of ethnicity is crucial to understanding how enemies are constructed. Prejudicial attitudes have the potential to influence our politicians, seep into our immigration systems, and affect our policies and criminal laws.
Keywords: Sociology, Criminology and Penology.